Seroprevalence of dengue in the general population of Hong Kong. Issue 9 (30th May 2013) - Lo, Constance LH; Yip, Shea Ping; Leung, Polly HM
Abstract Objectives To assess the extent of dengue virus exposure in the population. Methods In this seroepidemiological study, 685 blood samples were collected (from April 2007 to July 2009) from two subject groups: (i) 344 samples from anonymous blood donors of the Hong Kong Red Cross and (ii) 341 samples from healthy volunteers recruited from a university, a community centre and a hospital. Demographic information and travel history were collected for the second subject group. All blood samples were subjected to the PanBio Dengue IgG Indirect ELISA. Results Anti‐dengue virus IgG was detected in 1.6% of the blood samples. Individuals who visited countries in Southeast Asia in the past year were significantly associated with seropositivity (P = 0.03, OR 5.38, CI 1.13–25.54). Conclusions The overall dengue seroprevalence was 1.6%, and visit to Southeast Asia was the only independent predictor for seropositivity. Although the current situation is not alarming, frequent travel, presence of mosquito vector and emergence of local cases suggest that the risk of dengue virus infection within the local community cannot be overlooked, and continuous vigilance is warranted.